Turmeric Toxicity in A431 Epidermoid Cancer Cells Associates with Autophagy Degradation of Anti‐apoptotic and Anti‐autophagic p53 Mutant. (11th July 2014) - Thongrakard, Visa; Titone, Rossella; Follo, Carlo; Morani, Federica; Suksamrarn, Apichart; Tencomnao, Tewin; Isidoro, Ciro
<x xml:space="preserve">Abstract</x> The keratinocyte‐derived A431 Squamous Cell Carcinoma cells express the p53R273H mutant, which has been reported to inhibit apoptosis and autophagy. Here, we show that the crude extract of turmeric (Curcuma longa), similarly to its bioactive component Curcumin, could induce both apoptosis and autophagy in A431 cells, and these effects were concomitant with degradation of p53. Turmeric and curcumin also stimulated the activity of mTOR, which notoriously promotes cell growth and acts negatively on basal autophagy. Rapamycin‐mediated inhibition of mTOR synergized with turmeric and curcumin in causing p53 degradation, increased the production of autophagosomes and exacerbated cell toxicity leading to cell necrosis. Small‐interference mediated silencing of the autophagy proteins BECLIN 1 or ATG7 abrogated the induction of autophagy and largely rescued p53 stability in Turmeric‐treated or Curcumin‐treated cells, indicating that macroautophagy was mainly responsible for mutant p53 degradation. These data uncover a novel mechanism of turmeric and curcumin toxicity in chemoresistant cancer cells bearing mutant p53. Copyright © 2014 John Wiley & Sons, Ltd.